2022
DOI: 10.3390/pharmaceutics14102074
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Electrophysiological Changes in Pediatric Spinal Muscular Atrophy after 2 Years of Nusinersen Treatment

Abstract: In the new therapeutic era, disease-modifying treatment (nusinersen) has changed the natural evolution of spinal muscular atrophy (SMA), creating new phenotypes. The main purpose of the retrospective observational study was to explore changes in clinical evolution and electrophysiological data after 2 years of nusinersen treatment. We assessed distal compound motor action potential (CMAP) on the ulnar nerve and motor abilities in 34 SMA patients, aged between 1 and 16 years old, under nusinersen treatment, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“… 17 Axente et al revealed a notable increase in CMAP amplitudes after 2 years of nusinersen treatment, showing a significant correlation with the motor function evolution in SMA type 1 patients. 18 Kariyawasam et al also found that nusinersen treatment significantly increased CMAP in patients with SMA. 19 However, there is still limited literature reporting on whether nusinersen can alter peripheral motor nerve electrophysiology, which peripheral motor nerves may be affected, and the factors associated with such changes.…”
Section: Introductionmentioning
confidence: 93%
“… 17 Axente et al revealed a notable increase in CMAP amplitudes after 2 years of nusinersen treatment, showing a significant correlation with the motor function evolution in SMA type 1 patients. 18 Kariyawasam et al also found that nusinersen treatment significantly increased CMAP in patients with SMA. 19 However, there is still limited literature reporting on whether nusinersen can alter peripheral motor nerve electrophysiology, which peripheral motor nerves may be affected, and the factors associated with such changes.…”
Section: Introductionmentioning
confidence: 93%